Cloud Database-as-a-Service (DaaS) –ROI - Mateljan, Vladimir (Array, 2010)
Cloud computing concept has been presented with a overview of main services, cloud native and cloud capable relational / non-relational databases, and some advances and drawbacks of cloud Database-as-a-Service. Proposed Return On Investment(ROI)analysis outlineshow to decide andthe things to consider whether an application is suited for a cloud computing environment, on-premise (in- house) infrastructure or to outsourcing to managed services.